Seeking offsite help: a study of online support access for families of adolescents with depression - Chen Zhang; Lefan Zhou (Frontiers in Public Health)
BackgroundAs the smallest social unit, the family is the primary source of social support for adolescent patients to withstand chronic diseases. Several rehabilitation programs have found that involving family members in the treatment process can result in greater success. However, families struggle to provide adequate support for the recovery of adolescent patients when adolescent depression occurs.MethodsThis study examined the WeChat group for parents of adolescent patients in the “DuGuo” community, and used participatory observation, social network analysis, and extensive interviews to investigate the online support received by families with adolescent depression.ResultsIt was found that compared with physical diseases, adolescent depression recovery is a systemic problem, requiring all ecological contexts for adolescent growth to provide relative support. Under structural pressure, families with adolescent patients urgently require diversified social support such as medical consultation, emotional comfort, guidelines to return to school, and life planning. Insufficient offline social support leads parents to seek help from the Internet community.ConclusionWidespread factors such as communication constraints and hidden alienation in the nuclear family, render the parent–child relationship an important variable in combating depression. WeChat groups indeed provide a platform for parents with depressed children to seek help, but the real challenge for these parents is how online support from “off-site help” can be used in the family context and positively affect adolescent patients.